2010
DOI: 10.1017/s0959269510000335
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Ontario French

Abstract: A B S T R AC TThe present study is a Labovian sociolinguistic analysis of forms used to express the future tense in the spoken French of adolescents residing in Ontario, Canada. Two primary variants are examined: a) the periphrastic future (e.g. elle va partir); and b) the inflected future (e.g. elle partira). The general trend that emerges is that distribution rates of the periphrastic future are markedly higher than previous accounts of the variable and that many speakers are in fact categorical users of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 9 publications
3
51
0
Order By: Relevance
“…For the factor of temporal distance, studies of Acadian varieties of French (Comeau 2011;King & Nadasdi 2003) found tendencies in line with what might be expected, with the PF being favored in proximal contexts. For Laurentian French, some studies have shown no significant effect (Blondeau 2006;Grimm & Nadasdi 2011), whereas others have found a significant role for temporal distance, but one in which the results run counter to expectations (Poplack & Dion 2009;Poplack & Turpin 1999).…”
Section: Factormentioning
confidence: 80%
See 4 more Smart Citations
“…For the factor of temporal distance, studies of Acadian varieties of French (Comeau 2011;King & Nadasdi 2003) found tendencies in line with what might be expected, with the PF being favored in proximal contexts. For Laurentian French, some studies have shown no significant effect (Blondeau 2006;Grimm & Nadasdi 2011), whereas others have found a significant role for temporal distance, but one in which the results run counter to expectations (Poplack & Dion 2009;Poplack & Turpin 1999).…”
Section: Factormentioning
confidence: 80%
“…Although neither Blondeau (2006) nor Grimm and Nadasdi (2011) found a significant effect of LTI, both studies looked only at PF and IF. Grimm and Nadasdi (2011: 182) write that it is thus "not surprising that we found no effect for adverbial specification, since its role seems to be linked to the futurate present. "…”
Section: Factormentioning
confidence: 86%
See 3 more Smart Citations